2015
DOI: 10.1016/j.ymgme.2014.12.263
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of glycosaminoglycan assays for mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPS) are a group of lysosomal storage disorders caused by deficiency of the lysosomal enzymes essential for catabolism of glycosaminoglycans (GAGs). Accumulation of undegraded GAGs results in dysfunction of multiple organs, resulting in distinct clinical manifestations. A range of methods have been developed to measure specific GAGs in various human samples to investigate diagnosis, prognosis, pathogenesis, GAG interaction with other molecules, and monitoring therapeutic efficacy. We OPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 78 publications
(77 reference statements)
0
8
1
2
Order By: Relevance
“…The ratio of di-sulfated KS in total KS was significantly higher in MPS newborn patients compared to general newborns (p = 0.0001) (table 1). We have previously shown a secondary elevation of total KS and increase in ratio of di-sulfated KS in blood from older patients with other MPS types, where 40% for MPS II patients and 54% of MPS IVA had significantly higher levels of ratio di-sulfated KS in total KS (Shimada et al, 2015;Tomatsu et al, 2005;Tomatsu et al, 2014). We did not see a secondary elevation of KS in the MPS II newborn samples, possibly due to low accumulation during early stages of bone development.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The ratio of di-sulfated KS in total KS was significantly higher in MPS newborn patients compared to general newborns (p = 0.0001) (table 1). We have previously shown a secondary elevation of total KS and increase in ratio of di-sulfated KS in blood from older patients with other MPS types, where 40% for MPS II patients and 54% of MPS IVA had significantly higher levels of ratio di-sulfated KS in total KS (Shimada et al, 2015;Tomatsu et al, 2005;Tomatsu et al, 2014). We did not see a secondary elevation of KS in the MPS II newborn samples, possibly due to low accumulation during early stages of bone development.…”
Section: Discussioncontrasting
confidence: 42%
“…We have previously shown that blood from patients with other forms of MPS (IV, VI, and VII) contain elevated levels of other GAGs, but we do not have access to newborn DBS from such patients at this time and cannot directly determine GAG levels expected in newborn DBS from all MPS types (Tomatsu et al, 2005;Rowan et al, 2013;Shimada et al, 2014b;Tomatsu et al, 2014;Shimada et al, 2015). Nevertheless, based on data from older patients, this newborn screen is likely to capture patients with a severe form of any MPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomatsu et al (2005) have reported that keratan sulfate is elevated in both plasma and urine samples from patients with all mucopolysaccharidosis disorders (types I, II, III, IV, VI, and VII) compared to agematched controls. It was speculated that elevated heparan sulfate directly inhibits GALNS enzyme activity, resulting in a secondary elevation of keratan sulfate (Rowan et al 2013;Tomatsu et al 2014). This could explain the mild elevation of urine KS that was observed in MPS I and MPS II patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that KS is secondarily elevated in plasma (serum) and urine in several types of MPS and LSDs (in addition to MPS IV in which the deficient enzyme is directly involved in the catabolism of KS) . We previously proposed that secondary elevation of KS can be caused by several factors including the release of KS from damaged bone and cartilage . However, newborn DBS from MPS I, II, or III subjects showed no elevation of KS at birth .…”
Section: Discussionmentioning
confidence: 99%